Challenges of mainstreaming green infrastructure in built environment professions. Issue 4 (20th March 2020) - Zuniga-Teran, Adriana A.; Staddon, Chad; de Vito, Laura; Gerlak, Andrea K.; Ward, Sarah; Schoeman, Yolandi; Hart, Aimee; Booth, Giles
Abstract : Green infrastructure (GI) has been identified as a promising approach to help cities adapt to climate change through the provision of multiple ecosystem services. However, GI contributions to urban resilience will not be realized until it is more fully mainstreamed in the built environment and design professions. Here, we interrogate five key challenges for the effective implementation of GI: (1) design standards; (2) regulatory pathways; (3) socio-economic considerations; (4) financeability; and (5) innovation. Methods include a literature review, case studies, and interviews with resilience managers. We propose a people-centred and context-dependent approach to advance effective implementation of GI in urban planning. We highlight two underlying currents that run across all of the challenges – (1) the role of political will as a pre-condition for tackling all challenges holistically; and (2) the role of stakeholder engagement in achieving public support, harnessing funding, and maintaining and monitoring GI in the long term. Highlights: The effective implementation of GI is context-specific and should adhere to the basic principles of appropriate technology. Continuous community engagement is needed to ensure the inclusivity and multi-functionality of GI. Challenges to successful GI are intersectional and therefore cannot be addressed singly in isolation.